1‐Sulfonylated 1, 2, 3, 4‐tetrahydroquinoline‐6‐carboxylic acids as simple, readily‐accessible MCL‐1 inhibitors. Issue 8 (24th October 2022) - Chen, Lijia; Chan, Alexandria M.; Wilder, Paul T.; Fletcher, Steven
Abstract: MCL‐1 is a member of the BCL‐2 family of proteins that regulates the mitochondrial pathway of apoptosis. Overexpression of MCL‐1 is associated with the development and progression of a range of human cancers, and is also responsible for the onset of resistance to conventional chemotherapies. Although several MCL‐1 inhibitors have now advanced to clinical trials, recent suspensions and terminations reveal the urgency with which new inhibitor chemotypes must be discovered. Building on our previous studies of a chiral, isomeric lead, we report the discovery of a new chemotype to inhibit MCL‐1: 1‐sulfonylated 1, 2, 3, 4‐tetrahydroquinoline‐6‐carboxylic acid. The nature of the sulfonyl moiety contributed significantly to the resulting inhibitory ability. For example, transforming a phenylsulfonyl group into a 4‐chloro‐3, 5‐dimethylphenoxy)phenyl)sulfonyl moiety elicited more than a 73‐fold enhancement in inhibiton of MCL‐1, possibly through targeting the p2 pocket in the BH3‐binding groove, and so it is anticipated that further structure‐activity studies here will lead to continued improvements in binding. It should be underscored that this class of MCL‐1 inhibitors is readily accessible in four simple steps, is achiral and offers many avenues for optimization, all factors that are welcomed in the search for safe and effective inhibitors of this driver of cancer cell survival.